RESOURCE PROVISION OF THE CORPORATE INNOVATIVE SYSTEM OF THE DOMESTIC HITECH ENTEPRISES - D. A. Komonov; L. V. Mikhailova; A. A. Sazonov (Вестник университета)
The key resources, necessary for the process of transformation of the corporate innovation system of high-tech enterprises in the framework of the fourth industrial revolution «Industry 4.0» have been investigated. The main objective for enterprises is the creation of unique research centers, search laboratories, small innovative groups, and technology associations. A conclusion has been made, that domestic enterprises in modern conditions need to implement the procedure of analysis of existing business processes, including the life cycle of products and supply chains.